Association Between Serum 25-OH-Vitamin D and Diabetic Foot Ulcer in Patients With Type 2 Diabetes - Dai, Jiezhi; Yu, Min; Chen, Hua; Chai, Yimin (Frontiers in Nutrition, 2020)
Background: Vitamin D deficiency has been associated with an increased risk in several diabetic complications. We aimed to evaluate the association between vitamin D and diabetic foot ulcer (DFU) in patients with type 2 diabetes. Methods: 51 patients were included in the study and divided into two groups for study of vitamin D, cholesterol and triglycerides in blood serum on DFU. The association between vitamin D and DFU was measured by binary logistic regression analysis. The cut point of vitamin D for DFU was assessed by receiver operating characteristic curve. Results: Levels of 25-OH-vitamin D were lower in patients with DFU than in DM group (P<0.0001). The AUC of 25-OH-vitamin D was 0.8254 and had an optimal cut point value (13.68ng/ml) for the identification of DFU, with a sensitivity of 90% and a specificity of 66.67% in all patients. Multivariate logistic regression analysis indicated that the significant risk factors included 25-OH-vitamin D level (P=0.001, OR=0.618) and HDL-C level (P=0.038, OR=0.012). Conclusion: Low serum 25-OH-vitamin D level was associated with DFU. This indication was more specific than cholesterol and triglycerides levels.